2020
DOI: 10.1002/bio.3808
|View full text |Cite
|
Sign up to set email alerts
|

A coumarin‐based fluorescent probe for Hg2+ and its application in living cells and zebrafish

Abstract: Mercury (Hg) is a heavy metal with high toxicity and easy migration; it can be enriched through the food chain, and cause serious threats to the natural environment and human health. So, the development of a method that can be used to detect mercury ions (Hg2+) in the environment, in cells, and in organisms is very important. Here, a new 7‐hydroxycoumarin‐derived carbonothioate‐based probe (CC‐Hg) was designed and synthesized for detection of Hg2+. After addition of Hg2+, a large fluorescence enhancement was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…S14 †). On comparing with other probes listed in Table S1, † 6,7,15,42 CyP had good sensitivity to Hg 2+ . What's more, CyP has longer emission wavelengths (710 nm), and hence the probe was capable of imaging both the cells and animals in the subsequent experiments.…”
Section: Spectral Response Of Cyp Towards Hg 2+mentioning
confidence: 99%
“…S14 †). On comparing with other probes listed in Table S1, † 6,7,15,42 CyP had good sensitivity to Hg 2+ . What's more, CyP has longer emission wavelengths (710 nm), and hence the probe was capable of imaging both the cells and animals in the subsequent experiments.…”
Section: Spectral Response Of Cyp Towards Hg 2+mentioning
confidence: 99%
“…Recently, Li et al have reported 7-hydroxycoumarin-based carbonothioate derivative 111 (Figure 43) as a highly sensitive fluorescent probe for mercury ions with many practical applications [203]. The carbonothioate moiety acts as a selective and specific binder for Hg 2+ , and due to the good water solubility of probe 111, it can be used in cells or biological samples.…”
Section: Umbelliferone and 7-hydroxycoumarin-based Compounds As Probe...mentioning
confidence: 99%
“…Acceptor of FRET in HTS or monitoring of drug metabolites 108 [194] Fluorescent probe H2O2 109 [201] Fluorescent probe Hg 2+ 111 [203] Author Funding: This research received no external funding.…”
Section: Structure Biological Activity Molecular Target Name/ Numbermentioning
confidence: 99%
“…In compared to the reversible fluorescent sensors, the reaction-based fluorescent sensors showed better selectivity and specificity due to the structural changes occurred upon chemical reactions with the target analyte. The 7-hydroxycoumarin-derived carbonothioate-based sensor 66 (Figure 23) was designed and synthesized by Xiwei et al [94] for the detection of Hg 2+ at the maximum emission wavelength 455 nm in water medium. Upon interaction with Hg 2+ , sensor 66 showed a large fluorescence enhancement because of the strengthening of the intramolecular charge transfer (ICT) due to the Hg 2+ directed hydrolysis of 66 to form HgS and phenol.…”
Section: Reaction-based Chemosensorsmentioning
confidence: 99%